Relationship between body mass index and cardiorespiratory fitness to interpret health risks among sedentary university students from Northern India: A correlation study - Hardeep Singh; Vandana Esht; Mohammad A. Shaphe; Nikita Rathore; Aksh Chahal; Faizan Z. Kashoo (Elsevier, 2023)
Background: Obesity has been linked to a higher risk of developing cardiovascular diseases (CVD). The risk of CVD outcomes appears to be stratified by cardiorespiratory fitness (CRF). The study's goal was to determine the relationship between university students' Body Mass Index (BMI) and CRF. Methods: BMI and anthropometric measurements of sedentary male (n = 25) and female (n = 18) voluntary physiotherapy students, aged 18-25 years were taken. Pre- and post one minute (post1) and post 5 minutes (post2) six-minute walk test measurements of CRF-including respiration rate (breath per minute), oxygen saturation (in percentage), pulse rate (beat per minute), and blood pressure (mm Hg) were taken. The total distance (in meters) travelled in six minute (6MWDm) was recorded and entered into the formula: Vo2max = −9.824 + (0.072 x 6MWDm). Results: Males and females had median (IQR) values of BMI (20.75 and 22.15 kg/m2) and Vo2max (27.07 and 24.84 ml/kg/min) respectively. The data was divided into four groups based on body mass index categorization in relation to Vo2max, with negative coefficients of correlation in underweight (−0.18), overweight (−0.26), and obese (−0.33), and positive coefficients of correlation in normal (0.24) individuals. Wilcoxon signed rank test revealed post1 and post2 readings of respiration rate, oxygen saturation, pulse rate and systolic blood pressure were significantly higher than pre readings (p < 0.05). Conclusion: High obesity rate, weak cardio respiratory fitness and negative relationship between BMI and VO2Max indicate necessity of regular aerobic activities to improve health status among University students.